Are the data devouring us? - Santaella, Lucia (2021)
This article aims to define and discuss three interconnected concepts and practices, but, at the same time, irreducible: big data, datification and dataism. These are recent concepts that have been imposed due to the vertiginous increase of data that run at a unique speed on the internet. Discussions are developed to lead to more emphasis on dataism today criticized as a new form of religion. Its ambivalences, paradoxes and contradictions are highlighted, especially the paradox of the uninterrupted use of networks and the new contradictions of capitalism that are fueled by this use. The balance that oscillates between the user's desire and the harmful effects on the most recent logic of capitalism opens an abyss that this article places under reflection.